Controls on shallow gas distribution, migration, and associated geohazards in the Yangtze subaqueous delta and the Hangzhou Bay - Song, Lei; Fan, Daidu; Su, Jianfeng; Guo, Xingjie (Frontiers in Marine Science, 2023)
Shallow gas is generally extensively distributed in the Holocene muddy sediments and gas seepage has been increasingly reported to induce geohazards in coastal seas, but controls on gas distribution and migration remain elusive. This study explores gas distribution and migration in the Yangtze subaqueous delta and the Hangzhou Bay using high-resolution acoustic profiles and core data. Shallow gas is widely detected by the common presence of acoustic anomalous reflections including enhanced reflection, gas chimney, bright spot, acoustic blanking, and acoustic turbidity. The gas front depth is generally less than 17.5 m, and is meanly shallower in the Hangzhou Bay than in the Yangtze subaqueous delta because of relatively shallower water depth and coarser Holocene sediments in the Hangzhou Bay. Shallow gas is inferred to be a biogenic product, and its distribution is highly contingent on the Holocene stratal thickness and water depth. Active gas migration and seepages are evident, and recently increasing occurrences of gas seepage can be ascribed to global warming and seabed erosion due to sediment deficit. The findings warn us to pay more attention to the positive feedback loops of gas seepages with global warming and seabed erosion for the associated geohazard prediction and reduction, typically in the highly developed coastal regions.